The effect of organizational culture on employee satisfaction in Mercure Resort Sanur - I Putu Windu Tejayadi; I Nengah Laba; Gede Yoga Kharisma Pradana (Politeknik Negeri Bali, 2019)
When the organizational culture works optimally at a hotel it should have a significant effect on the satisfaction of all parties, including employee satisfaction. Thus the hypothesis of this study confirms that organizational culture significantly influences employee satisfaction at Mercure Resort Sanur, Denpasar, Bali. All primary data were obtained through 48 respondents using the instrument in the form of a questionnaire. All data were analyzed quantitatively to determine the magnitude of the influence of organizational culture on employee satisfaction Mercure Resort Sanur. The results showed that the organizational culture of employee satisfaction at Mercure Resort Sanur had a significant effect. The significance level of the organizational culture of employee satisfaction at Mercure Resort Sanur reaches 0.002, smaller than alpha 0.05. Thus, the research hypothesis is proven.